Effectiveness of Distraction Therapy on Children's Pain Perceptions During Peripheral Venous Cannulation at Pediatric Teaching Hospital in Erbil City - Norhan Zeki Shaker; Ari Ahmed Taha (Hawler Medical University, 2018)
Background and objective: Relief of pain is a basic need and right of all children; effective pain management requires health professionals to be able to apply a number of interventions to achieve optimal results. The current study aimed to discover the effects of distraction therapy on children's pain perception during peripheral venous cannulation. Methods: A quasi-experimental study was carried out at emergency unit of Raparin       Paediatric Teaching Hospital in Erbil city, Iraq. Data collection occurred from Feb 22, 2016  to May 25, 2016. A non-probability purposive sample of 120 children who were undergoing peripheral venous cannulation are recruited for the study. Data was collected through a questionnaire format and a standard observational checklist Assessments of the face, legs, activity including crying, and the console ability (FLACC) pain rating scale were used to assess the pain perception of child. A cartoon and animation video films were used by the researcher, as distraction therapy for the intervention group, while the control group received traditional routine care by the nurses. The statistical package for social science (SPSS, Version 22) was used for data processing and statistical analysis such as   frequency, percentage, mean, SD, F-test, paired t-test, chi-square and Fisher exact test. Results: The study found that the majority of children in the intervention group experienced mild discomfort and pain while the majority of children in the control group experienced severe pain or discomfort or both. The results revealed that there were very highly significant differences in the levels of pain perception between intervention and control groups. Conclusion: Application of distraction therapy could have a positive effectiveness for relieving pain among preschool age children during peripheral venous cannulation.